Psycho-social factors as correlates of job performance of women in the print media in Southwestern, Nigeria (2014)
The effect of communication in any society cannot be ignored. Media play great role in shaping and correcting the vices of the society. The presence of women in the print media has shown that they are relevant and up to the rigorous task of gathering news and meeting deadlines. These they have done in living up to expectations in their various media houses. This thus raises the concern of what could be attributable for this trend of women working in such a demanding profession. Could it be that these women have developed some psycho-social attributes emotional intelligence (EI), self-concept (SC), self-efficacy, (SE) (mentoring, age at job entry, marital status, educational background, socio economic status and number of children), ability to work under pressure and newsworthiness which could have accounted for their job performance? This study, therefore, investigates some psycho-social factors as they correlate with job performance of women in the print media in Southwestern Nigeria. The descriptive survey research design of the ex post facto type was adopted. The total enumeration and stratified random sampling techniques were adopted using 549 women professionals from 12 purposively selected print media houses. A 5 Likert scale questionnaire was administered and complemented with jour sessions of in-depth interviews with selected women in the print media. Data were analysed using descriptive statistics, Pearson Product moment correlation, multiple regression and content analysis. The findings show that EI, SE, SC mentoring, age at job entry, marital status, educational background, socio economic status and number of children correlated with job performance of women in the media. The study shows that Psycho-social factors influence job performance of women in the print media in Southwestern Nigeria and priority should be given to these factors while number of children does not influence job performance of these women.